Development of Cultural Tourism in Mepar Village, Lingga Regency in Tourism Planning - Renggi Erwanda Siregar; Reinold Palit; Yuanita FD Sidabutar; Raflis Tanjung (Budapest International Research and Critics University, 2022)
Lingga Regency is a new regency that is developing. The acceleration of regional development is strongly influenced by the accessibility and availability of infrastructure to support the development of the potential of natural resources in the Lingga Regency area. One of the supports for the development of development funds in Lingga Regency is the selling value of tourist objects. In this case, Lingga Regency has a long history associated with the development of the Malay kingdom. Not only in the form of mere history in Lingga Regency, it also leaves several historical heritage objects which are still preserved by the local government and local communities. One of the famous historical heritage attractions in Lingga Regency is Mepar Island. Mepar Island is a small island located in front of the capital city of Daik. on the island of Mepar there is a village called Mepar Village. Mepar village is the center of tourist attraction on the island of Mepar. Mepar village was one of the defensive fortifications during the Riau-Lingga kingdom, leaving several historical relics, one of which was the remains of the fortifications, the tomb of heroes and weapons of war in the form of cannons. This is what makes Mepar Village, Lingga Regency, a special attraction for people who will visit these tourist attractions. In this case, it is necessary to improve the quality and efficiency of the tourism service system in Mepar Village so that it attracts more visitors' attention. So that the results of increased tourist visits will make the tourist attraction in Mepar Village more developed and become a tourist that can be known by foreign tourists.